Assessing and monitoring physical performance using wearable technologies in volleyball players - Sousa, A. C.; Marques, D. L.; Marinho, D. A.; Neiva, H. P.; Marques, M. C. (Applied Sciences, 2023)
Wearable devices have been used to assess and monitor volleyball performance. Given the diversity of technologies used and the variables measured, this study aimed to synthesize and review the wearable technology used to assess and monitor physical performance in volleyball players. A comprehensive search of published articles was performed in the following databases: Web of Science, PubMed, and Scopus, up to 23 October 2022. Studies with volleyball players of any age that used a wearable device to assess or monitor physical performance (e.g., jump height) were included. Nine studies conducted with male or female volleyball players were included. The participants` age ranged between 16 and 32 years. Eight studies used Triaxial IMU, and one study used Vertec IMU. The performance analysis was based on vertical jump ability (n = 7) and overall volleyball performance (n = 2). Of the nine studies analyzed, 75% of the studies revealed blinding at the participant level and allocation concealment, and 95% reported a low risk of bias in the outcome assessment. This study shows that monitoring and assessing vertical jump ability through wearable devices is an increasing procedure in volleyball. Therefore, as jump height is a critical variable in athletic performance in volleyball, coaches and researchers might consider using wearable devices to assess and monitor physical performance changes in volleyball players.